An efficient and lightweight identity-based scheme for secure communication in clustered wireless sensor networks. (April 2022) - Mezrag, Fares; Bitam, Salim; Mellouk, Abdelhamid
Abstract: Clustered Wireless Sensor Networks (CWSNs) are typically deployed in unsecured or even hostile areas, making them vulnerable to many cyber-attacks and security threats that adversely affect their performance. Furthermore, the design of an efficient cryptographic scheme for CWSN is challenging due to the dynamic nature of the network and resource-constrained sensor devices. The paper presents a new identity-based authentication and key agreement scheme for CWSNs called IBAKAS, which combines Elliptic Curve Cryptography (ECC) and Identity-Based Cryptography (IBC) to provide mutual authentication and establish secret session keys over insecure channels. IBAKAS achieves all desirable security properties of key agreement and prevents specific cyber-attacks on CWSN. Moreover, the formal security of the proposed scheme is verified using the AVISPA tool. Comparison with existing relevant schemes shows that the proposed scheme decreases computational and communication overheads, saves keys storage space and prolongs the network lifetime by reducing the energy consumption of the sensor node.